Economics of undersea resources - Ingo Walter (Intereconomics, 1977)
The open seas have recently become recognized as a major resource on which the world is likely to grow increasingly dependent in the years ahead. With regard to their exploitation questions of efficiency and equity have arisen that are being fought out primarily within the UN Conference on the Law of the Sea the sixth round of which ended last month, once again without any concrete results. Professor Walter explains what is at stake.
Keywords: 330; Law of the Sea